2022
DOI: 10.1093/gastro/goac036
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the risk factors for severe complications and surgery of intestinal foreign bodies in adults: a single-center experience with 180 cases

Abstract: Background Foreign bodies (FBs) lodged in the intestine or causing intestinal complications are uncommon in clinical practice but may pose diagnostic difficulties and prove life-threatening. This study aimed to evaluate the risk factors for severe complications and surgery to aid clinicians in the diagnosis and management of intestinal FBs. Methods We performed a retrospective analysis of patients in whom FBs were lodged in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 51 publications
(56 reference statements)
1
2
0
Order By: Relevance
“…Such difficult and unusual cases require a close interdisciplinary communication and collaboration between gastroenterologists and surgeons. Our case confirmed that the foreign bodies were particularly concentrated in areas with angled regions as the duodenum or sigmoid colon and in the area of the most common impaction point orally of the ileocecal valve [ 9 , 12 ]. Because of the acute course of the disease, we concentrated on the obvious perforation, as ingestion of large foreign bodies is principally associated with perforation of hollow organs.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Such difficult and unusual cases require a close interdisciplinary communication and collaboration between gastroenterologists and surgeons. Our case confirmed that the foreign bodies were particularly concentrated in areas with angled regions as the duodenum or sigmoid colon and in the area of the most common impaction point orally of the ileocecal valve [ 9 , 12 ]. Because of the acute course of the disease, we concentrated on the obvious perforation, as ingestion of large foreign bodies is principally associated with perforation of hollow organs.…”
Section: Discussionsupporting
confidence: 76%
“…As in our case, previous reports also showed that plain radiographs failed to reveal the presence of intra-abdominal free air. CT scans demonstrated the highest sensitivity of imaging techniques in detecting intestinal foreign bodies [ 9 ]. In our case CT could not visualize the fistulas, probably because of artefacts caused by the foreign bodies.…”
Section: Discussionmentioning
confidence: 99%
“…[18] CT shows a sensitivity between 42 to 78% in the detection of FB and is paramount to making a correct diagnosis [11] [14]. It allows identifying the localization of the FB, the shape and its relation with the surrounding organs and eventual complications, which helps plan surgery [11] [12]. It makes it possible to recognize an inflammatory reaction surrounding the foreign body, linear objects (eventually encircled by a thickened intestinal wall), fat infiltration, peritoneum and intra-abdominal abscess when perforation occurs [7] If a CT scan detects any foreign bodies stuck in the upper part of the small intestine or large intestine, then endoscopy should be done for diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Foreign objects lodged in the esophagus must be emergently removed for their life-threatening complications. [12] No definite guidelines are available for objects that pass through the pylorus, the usual therapeutic approach is a watchful waiting within 2-3 weeks until its expulsion. If watchful waiting does not lead to the passage of these objects to the stomach the recommendations suggest an endoscopic removal.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the site of penetration, the clinical presentation may mimic more common medical conditions, e.g., peptic ulcer disease or gastritis if the bristle lodges in the stomach, or pancreatitis if the bristle is in the pancreas or duodenum [9]. Micro-perforations of the small bowel are usually subtle and subacute in nature and present with less severe symptoms than perforations in other parts of the gastrointestinal tract [10][11][12].…”
Section: Discussionmentioning
confidence: 99%